Medical consultations per capita in the Peruvian health system, 2019. Towards a new description of the Peruvian health system - Murillo-Peña, Juan Pablo (2023)
Introduction. The objective of the study is to contribute with a new perspective about the peruvian health system, based on the production of public goods in health. Methods. For this purpose, we calculated the per capita average of health encounters produced by the peruvian health system at the national, regional and provincial levels. Information was collected on the number of medical encounters, registered at the open data sources of the National Health Superintendence (SUSALUD), the Public Health Insurance (SIS), and the Health Social Insurance (EsSalud) for year 2019. Results. The national average of medical encounters per capita was 1.8, with a great variability of values at the regional level (2.9 to 0.8). In the case of the provinces, a first upper quartile was found, which group 50 provinces with values between 5.52 and 1.75 and concentrate 55% of the Peruvian population and 71.3% of all medical encounters produced by the health system. A second quartile groups 47 provinces, with values between 1.73 - 1.33; and two lower quartiles that group 95 provinces with values between 1.32 and 0.08. We showed an association between per capita medical encounters at the regional level and the socio-economic variables analyzed, in particular the Density of Physicians per 1000 population (R2: 0.64, p-value= 0.000) and the regional gross domestic product per capita (R2 : 0.59, p-value=0.000).  Conclusion. Medical encounters per capita is a useful indicator, that allows us to identify better served territories, with higher definition than other structure indicators (doctors per 1000 people; number of facilities).